Platelet-Rich Plasma Releasate Promotes Early Healing in Tendon After Acute Injury. Issue 4 (19th April 2021) - Yu, Tung-Yang; Pang, Jong-Hwei S.; Lin, Li-Ping; Cheng, Ju-Wen; Liu, Shih-Jung; Tsai, Wen-Chung
Background: Acute tendon injury can limit motion and thereby inhibit tendon healing. Positive results have been found after the use of platelet-rich plasma (PRP) to treat tendon injury; however, the early effects of PRP on tendon regeneration are not known. Purpose/Hypothesis: The purpose of this study was to evaluate the effects of PRP releasate (PRPr) on the early stages of tendon healing in a rat partial tenotomy model. It was hypothesized that PRPr can promote early healing of an Achilles tendon in rats. Study Design: Controlled laboratory study. Methods: PRP was prepared by a 2-step method of manual platelet concentration from 10 rats. PRPr was isolated from the clotted preparation after activation by thrombin and was applied to an Achilles tendon on 1 side of 30 rats on the second day after partial tenotomy, with normal saline used as the control on the other side. Achilles tendon samples were harvested 5 and 10 days after tenotomy. At each time point, 15 Achilles tendon samples were obtained, of which 5 samples were evaluated by Masson trichrome staining, apoptosis, and cell proliferation, while the other 10 samples were tested for tensile strength using a material testing machine. Results: Compared with saline-treated control tendons, the PRPr-treated tendons showed increased collagen synthesis near the cut edge and fewer apoptotic cells ( P = .01). An immunohistochemical analysis revealed more Ki-67–positive cells but fewer cluster of differentiation (CD) 68 + (ED1 + ) macrophages in PRPr tendons compared with saline-treated tendons ( P < .01). Tendons treated with PRPr also showed higher ultimate tensile strength than those treated with saline ( P = .03). Conclusion: PRPr treatment promotes tissue recovery in the early phase of tendon healing by stimulating tendon cell proliferation and collagen production while inhibiting cell apoptosis and CD68 + (ED1 + ) macrophage infiltration. Clinical Relevance: These findings suggest that with PRPr treatment, higher loads can be applied to the healing tendon at an earlier time, which can help the patient resume activity earlier.